Aromatic (Co)polycarbonates bearing pendant norbornenyl groups: Synthesis, characterization and post-polymerization modification - Talanikar, Aniket A.; Nagane, Samadhan S.; Wadgaonkar, Prakash P.; Rashinkar, Gajanan S. (High Performance Polymers, 2024)
A homo- and three co-polycarbonates (PC-NBs) bearing pendant norbornenyl groups were synthesized via solution polycondensation of triphosgene with 4, 4'-(bicyclo (2.2.1) hept-5-en-2 yl methylene) bis (2-methoxyphenol) (BPA-NB) or various mol % compositions of BPA-NB and bisphenol-A, respectively. 1H-NMR spectroscopy confirmed the chemical structure and composition of PC-NBs. Inherent viscosity and number-average molecular weight (Mn) values of PC-NBs were in the range 0.44 - 0.64 dL g-1 and 21,800 - 34,100 g mol-1, respectively, indicating the formation of polymers of medium to reasonably high molecular weights. Tough, transparent, and flexible films of PC-NBs could be cast from chloroform solution. X-Ray diffraction studies indicated the amorphous nature of PC-NBs. Glass transition temperature (Tg) values, determined by DSC analysis, of PC-NBs were in the range 154 - 175 degrees C and Tg values increased with the increase in mol % of BPA-NB. The post-polymerization modification of a representative PC-NB was demonstrated using 3,6-diphenyl-1,2,4,5-tetrazine via tetrazine-ene reaction.
Keywords: (co)polycarbonates; norbornenyl groups; post-polymerization modification; tetrazine-ene click reaction; thermoplastics